Different physiological responses of cyanobacteria to ultraviolet‐B radiation under iron‐replete and iron‐deficient conditions: Implications for underestimating the negative effects of UV‐B radiation. Issue 2 (7th March 2017) - Li, Zheng‐Ke; Dai, Guo‐Zheng; Juneau, Philippe; Qiu, Bao‐Sheng
Abstract : Iron deficiency has been considered one of the main limiting factors of phytoplankton productivity in some aquatic systems including oceans and lakes. Concomitantly, solar ultraviolet‐B radiation has been shown to have both deleterious and positive impacts on phytoplankton productivity. However, how iron‐deficient cyanobacteria respond to UV‐B radiation has been largely overlooked in aquatic systems. In this study, physiological responses of four cyanobacterial strains ( Microcystis and Synechococcus ), which are widely distributed in freshwater or marine systems, were investigated under different UV‐B irradiances and iron conditions. The growth, photosynthetic pigment composition, photosynthetic activity, and nonphotochemical quenching of the different cyanobacterial strains were drastically altered by enhanced UV‐B radiation under iron‐deficient conditions, but were less affected under iron‐replete conditions. Intracellular reactive oxygen species (ROS) and iron content increased and decreased, respectively, with increased UV‐B radiation under iron‐deficient conditions for both Microcystis aeruginosa FACHB 912 and Synechococcus sp. WH8102. On the contrary, intracellular ROS and iron content of these two strains remained constant and increased, respectively, with increased UV‐B radiation under iron‐replete conditions. These results indicate that iron‐deficient cyanobacteria are more susceptible to enhanced UV‐B radiation. Therefore, UV‐B radiation probably plays an important role in influencing primary productivity in iron‐deficient aquatic systems, suggesting that its effects on the phytoplankton productivity may be underestimated in iron‐deficient regions around the world.